CONCEPTS FOR TEACHING SPEAKING IN THE ENGLISH LANGUAGE CLASSROOM - Bakhtiyorova, Gulnora (MMIT Proceedings, 2023)
To be able to communicate fluently in a foreign language is the number one goal for many language learners. However, it seems that the teaching of oral skills in language classrooms does not have an important role. There are many reasons: the higher status of written language, teaching to the tests (of written language), teaching the textbook (with emphasis on written language), and lack of knowledge of how to teach speaking. The purpose of the article is to discuss the issue of how foreign language (FL) speaking can be taught based on 1) how speaking is learned and 2) how speaking proficiency is defined. More specifically, 1) How do learning theories translate into teaching speaking at classroom level? And 2) What is the significance of the current understanding of language proficiency as reflected in the models of communicative competence and the Common European Framework (Council of Europe, 2001) and its Companion Volume with New Descriptors (Council of Europe, 2018) to the teaching of speaking in formal foreign language contexts? On the basis of the theoretical and research reviews, some pedagogical implications and suggestions for research are provided. The pedagogical implications concern the teaching of fluency and formulaic sequences, the teaching of spoken grammar, the teaching of linguistic, sociolinguistic and pragmatic competences. Classroom applications of the sociocultural theory include pair and group work, communicative activities with opportunities for the negotiation of meaning, and creative spoken production. It is suggested that teachers’ pedagogical content knowledge (PCK) be applied as a means to integrate theory with classroom applications. Suggestions for related research are provided.